A Strategic Study on the Effective Application of Flipped Classroom Teaching Method in World Music Appreciation Classroom - Qiang, Fu; Hirunrux , Sakchai; Yukolthonwong, Supot (Journal of Roi Kaensarn Academi, 2024)
With the proposal of the concept of "quality education", public world music appreciation courses in universities are gradually being valued. More and more universities are offering world music appreciation elective courses, aiming to stimulate students’ interest in learning and improve their appreciation level and music literacy. In recent years, with the rapid development of technology, the emergence of large-scale online open courses has led to corresponding changes in the teaching mode of existing world music appreciation courses. In this era of advocating knowledge sharing, students can learn and share high-quality teaching resources from well-known universities and excellent teachers through flipped classroom. With the arrival of the era of educational informatization, traditional world music appreciation teaching in universities has been restructured through continuous innovation and change in technology. Classroom teaching methods pay more attention to interactive communication and independent learning among college students; Classroom evaluation methods have also become more diverse and diverse. Based on this, by analyzing the "flipped classroom".Research on achieving interactive teaching of world music appreciation in universities, constructing and innovating a flipped classroom teaching model for world music appreciation in universities, and seeking a practical path for intelligent physical education classroom teaching in universities, in order to stimulate the enthusiasm and initiative of college students in learning world music appreciation courses and meet their personalized development needs.